Microenvironments Designed to Support Growth and Function of Neuronal Cells - Farrukh, Aleeza; Zhao, Shifang; del Campo, Aránzazu (Frontiers in Materials, 2018)
Strategies for neural tissue repair heavily depend on our ability to temporally reconstruct the natural cellular microenvironment of neural cells. Biomaterials play a fundamental role in this context, as they provide the mechanical support for cells to attach and migrate to the injury site, as well as fundamental signals for differentiation. This review describes how different cellular processes (attachment, proliferation, and (directional) migration and differentiation) have been supported by different material parameters, in vitro and in vivo. Although incipient guidelines for biomaterial design become visible, literature in the field remains rather phenomenological. As in other fields of tissue regeneration, progress will depend on more systematic studies on cell-materials response, better understanding on how cells behave and understand signals in their natural milieu from neurobiology studies, and the translation of this knowledge into engineered microenvironments for clinical use.